2023
DOI: 10.1097/icl.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction, Visual Outcomes, and Regression Analysis in Post-LASIK Patients Implanted With Multifocal, EDOF, or Monofocal IOLs

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The visual quality in terms of contrast sensitivity was reported to decrease in cataract patients after multifocal IOL implantation, possibly due to the distribution of light to different focal points ( 46 ). However, Bucci et al reported that EDOF IOLs did not significantly decrease contrast sensitivity in cataract patients after LASIK compared with monofocal IOLs ( 47 ).…”
Section: Emerging Challenges and A Paradigm Shift In The Management O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The visual quality in terms of contrast sensitivity was reported to decrease in cataract patients after multifocal IOL implantation, possibly due to the distribution of light to different focal points ( 46 ). However, Bucci et al reported that EDOF IOLs did not significantly decrease contrast sensitivity in cataract patients after LASIK compared with monofocal IOLs ( 47 ).…”
Section: Emerging Challenges and A Paradigm Shift In The Management O...mentioning
confidence: 99%
“…The visual quality in terms of contrast sensitivity was reported to decrease in cataract patients after multifocal IOL implantation, possibly due to the distribution of light to different focal points (46). However, Bucci et (47). Despite concerns about visual quality, for highly myopic eyes with special anatomical features, ophthalmologists should select the appropriate IOL carefully, offering long-term stability.…”
Section: Appropriate Iol Selectionmentioning
confidence: 99%
“…Several reports have compared the differences in visual quality and photic phenomena after implantation of different types of presbyopia-correcting IOLs in patients who have undergone myopic LASIK or PRK 11 , 12 . However, the most suitable type of IOL for these patients has yet to be ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…В этой связи необходимо отметить, что к настоящему моменту в литературе накоплен определенный опыт сравнительной оценки МОФИОЛ, МУФИОЛ и ЭДОФ, указывающий на высокую взаимосвязь прогнозируемых и полученных в рамках послеоперационного обследования клинических и функциональных результатов. При этом указывается, что общая оценка клинической эффективности ЭДОФ требует дальнейшего изучения, особенно с позиции практического применения у конкретного контингента пациентов (например, у лиц зрительно-напряженного труда -профессиональных пользователей персональных компьютеров) [10,[29][30][31][32][33].…”
unclassified